The Concept of Islamic Education Living Together in Diversity: A Study of Hamka's Perspective to Support the Achievement of the SDGs - Muhammad Dwi Fajri (Profetika: Jurnal Studi Islam, 2024)
Objective: Diversity is an inevitable social reality that encompasses differences in religion, culture, ethnicity, and language. These differences can be sources of both strength and conflict. In this context, Islamic education plays a strategic role in shaping individuals who can live harmoniously within a pluralistic society. This study aims to explore Hamka's thoughts on Islamic education as a means of fostering peaceful coexistence in diversity, emphasizing the multicultural values embedded in Islamic teachings to support the achievement of the Sustainable Development Goals (SDGs). Theoretical framework: The theoretical framework of this research is based on Hamka’s educational philosophy, which highlights moral education (Akhlaq), tolerance, and social harmony. This study also incorporates perspectives from multicultural education theories, particularly in the context of religious pluralism and social cohesion. Literature Review: The literature review examines previous studies on Hamka's contributions to Islamic education, multiculturalism in Islam, and the role of education in promoting tolerance and social justice. Methods: This study employs a qualitative method with a hermeneutic approach, analyzing Hamka's works, including Akhlaqul Karimah and his Quranic interpretations, as primary sources. Secondary data is obtained from academic articles, journals, and relevant references. Data collection is conducted through literature study, while data analysis follows the process of data condensation, display, and conclusion drawing. Results: The results indicate that Hamka emphasizes the integration of justice, tolerance, brotherhood, and respect for differences in Islamic education. His perspective aligns with SDG 4 (Quality Education) and SDG 16 (Peace, Justice, and Strong Institutions), advocating for an educational system that fosters social harmony and national unity amidst challenges such as radicalization and polarization. Hamka also provides practical guidance on managing diversity based on the principles of Tawhid (monotheism) and respect for human rights. Implications: The implications of this research highlight the need for an inclusive Islamic education curriculum that aligns with the multicultural realities of Indonesian society. Novelty: The novelty of this research lies in its systematic integration of Hamka’s educational philosophy with the SDGs framework, offering a unique perspective on how Islamic teachings can contribute to multicultural education and global peace.